Chemical and kinematic complexity of the very young star-forming region Serpens Main observed with ALMA. Issue Volume 13:Issue S332(2017) (4th September 2018) - Tychoniec, Łukasz; Hull, Charles L. H.; Tobin, John J.; van Dishoeck, Ewine F.
Abstract: The youngest low-mass protostars are known to be chemically rich, accreting matter most vigorously, and producing the most powerful outflows. Molecules are unique tracers of these phenomena. We use ALMA to study several outflow sources in the Serpens Main region. The most luminous source, Ser-SMM1, shows the richest chemical composition, but some complex molecules are also present in S68N. No emission from complex organics is detected toward Ser-emb 8N, which is the least luminous in the sample. We discuss whether these differences reflect an evolutionary effect or whether they are due to different physical structures. We also analyze the outflow structure from these young protostars by comparing emission of CO and SiO. EHV molecular jets originating from SMM1-a, b and Ser-emb 8N contrast with no such activity from S68N, which on the other hand presents a complex outflow structure.